On a Periodic Capital Injection and Barrier Dividend Strategy in the Compound Poisson Risk Model - Wenguang Yu; Peng Guo; Qi Wang; Guofeng Guan; Qing Yang; Yujuan Huang; Xinliang Yu; Boyi Jin; Chaoran Cui (Mathematics, 2020)
In this paper, we assume that the reserve level of an insurance company can only be observed at discrete time points, then a new risk model is proposed by introducing a periodic capital injection strategy and a barrier dividend strategy into the classical risk model. We derive the equations and the boundary conditions satisfied by the Gerber-Shiu function, the expected discounted capital injection function and the expected discounted dividend function by assuming that the observation interval and claim amount are exponentially distributed, respectively. Numerical examples are also given to further analyze the influence of relevant parameters on the actuarial function of the risk model.